Liver abscesses with pyopericardium: Laparoscopic management in a preterm neonate - Ravishankaran Praveen; Rajamani G (Wolters Kluwer Medknow Publications, 2010)
We report a 28-day-old neonate presenting with signs of fever, abdominal distension, and refusal to feed. The baby was diagnosed to have multiple liver abscesses which ruptured and a tract lead to the pericardium resulting in a pyo-pericardium. Laparoscopic drainage of the abscess cavities and the pyo-pericardium was performed. An extensive search of the literature revealed that this case is the youngest one to have undergone such simultaneous laparoscopic drainage.